2012
DOI: 10.3747/co.19.1016
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction for Breast Cancer—A Systematic Review and Meta-Analysis

Abstract: ConclusionsThere is some evidence for the effectiveness of mbsr in improving psychological health in breast cancer patients, but more rcts are needed to underpin those results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(161 citation statements)
references
References 39 publications
6
145
0
10
Order By: Relevance
“…As previous reviews also mentioned no study reported adverse events, and reasons for dropouts were poorly reported. Those findings are unsatisfying, because safety is a major focus in the evaluation of therapies [29].…”
Section: Resultsmentioning
confidence: 96%
“…As previous reviews also mentioned no study reported adverse events, and reasons for dropouts were poorly reported. Those findings are unsatisfying, because safety is a major focus in the evaluation of therapies [29].…”
Section: Resultsmentioning
confidence: 96%
“…In addition to improving a range of variables related to psychosocial dimensions and quality of life [27][28][29][30], research indicates that mindfulness-based interventions (MBIs) can alleviate physical symptoms for sufferers of some disorders [29,31,32]. Grossman et al [29] meta-analysis found moderate-to-large effect sizes on physical variables in both controlled and observational studies.…”
Section: Mindfulness As a Treatment For Physical Symptomsmentioning
confidence: 99%
“…For follow-up effect size, the difference between the mean follow-up value and the mean baseline value divided by the baseline standard deviation was calculated. Figure 1 for FEV 1 , Figure 2 for FEV [25][26][27][28][29][30][31][32][33][34][35] and Figure 3 for STAI State depict the data across baseline, intervention, and follow-up phases.…”
Section: Pulmonary Function and State Anxietymentioning
confidence: 99%
“…A number of systematic reviews suggest that MBSR is effective for a variety of psychosocial cancer symptoms, such as stress, depression, anxiety, and reduced quality of life. 23,24 The day care clinic combines MBSR with elements of the mind-body medicine cancer program of the BensonHenry Mind/Body Medical Institute at Harvard Medical School, which is rooted in psychoneuroendocrinology and focuses on relaxation techniques, exercise, cognitive restructuring, diet, and social support. 25 In addition to elements of these 2 programs, naturopathic methods of self-regulation and self-care are incorporated, that is, cataplasms, phytotherapy, massages, and hydrotherapy.…”
Section: Conceptual Frameworkmentioning
confidence: 99%